Nanotechnology: Applications in Medicine and Beyond - J, John Kiran; Dahiya, Kiran; Deepak, Chordiya Pratiksha; Urvashi,; Patel, Rutul; Dash, Chandini; Mittal, Avi (Recent Developments in Chemistry and Biochemistry Research Vol. 8, 2024)
Nanotechnology is the manipulation of materials at the nanoscale, which ranges from 1 to 100 nanometres and has advanced applications in industries such as biology, electronics, transportation, energy, agriculture, cosmetics, space exploration, and environmental research. Nanotechnology in medicine allows for early illness detection, prevention, diagnosis, tailored therapy, and monitoring. Some notable uses include gold nanoparticles as biosensors for genetic sequencing, carbon nanotubes for cancer diagnosis, and nanoparticles in stem cell research. Nanotechnology is integrated into genetic analysis via the use of nanoparticles in atomic force microscopy and quantum dot fluorescence in situ hybridisation. Furthermore, nanoparticles improve polymerase chain reaction (PCR) procedures and function as contrast agents in imaging modalities like ultrasound and MRI. Beyond healthcare, this technology has a transformational influence on contemporary society. Improved nutrient delivery and stress tolerance in crops are among its agricultural advantages, as are food safety, quality, and nutrient bioavailability in the food business. Nanotechnology development has the possibility of addressing major global concerns while also improving quality of life and promoting sustainability.